2020
DOI: 10.1097/nne.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Knowledge and Value on Quality of Supportive Peer Feedback

Abstract: Background: Motivational barriers and lack of knowledge about peer review inhibit creation of supportive peer feedback between nursing students. Purpose: The purpose of this study was to examine the effects of knowledge of peer-review practices and value for the process of creating supportive peer feedback on the quality of feedback nursing students create for their peers. Method: Data from 155 graduate nursing students were analyzed in this quasi-experimental, repeated-measures design, using analysis of covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…The previous study revealed that high levels of value for providing peer feedback significantly improved quality of feedback produced by students. 7 A single data collection instrument measured students' knowledge of peer-review principles and asked them to rate their levels of expectancy for success, value, and sense of cost related to learning to provide high-quality, supportive feedback to peers. In addition, they were asked 2 open-ended questions about what factors motivate and demotivate them to provide high-quality, supportive feedback to peers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous study revealed that high levels of value for providing peer feedback significantly improved quality of feedback produced by students. 7 A single data collection instrument measured students' knowledge of peer-review principles and asked them to rate their levels of expectancy for success, value, and sense of cost related to learning to provide high-quality, supportive feedback to peers. In addition, they were asked 2 open-ended questions about what factors motivate and demotivate them to provide high-quality, supportive feedback to peers.…”
Section: Methodsmentioning
confidence: 99%
“…The authors combined quantitative results from the previous study 7 (specifically, value scores for providing supportive peer feedback) with qualitative data (students' perceptions of factors that motivated or demotivated them to provide supportive peer feedback). Value was measured by 4 survey items on a Likert scale ranging from 1 (strongly disagree) to 6 (strongly agree) and yielded a high level of internal consistency, with a Cronbach's α = .90.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…How nurse educators time, structure, and implement peer review in courses can greatly impact its success. Tornwall et al 15 recommend peer review activities be designed to explicitly guide students in giving high-quality and supportive feedback instead of asking them to give one another broad feedback or edits. They further suggest peer review activities should be designed to provide students with ample time to give feedback and make revisions.…”
mentioning
confidence: 99%